Prayer books and piety in late medieval and early modern Europe = Gebetbücher und Frömmigkeit in Spätmittelalter und Früher Neuzeit - Crăciun, Maria; Leppin, Volker; Luffy, Katalin; Wien, Ulrich Andreas (Refo500 academic studies, 2023)
Maria Crăciun (Babeş-Bolyai University, Cluj): Worship of the Written Word:. Books and Piety in Late Medieval and Early Modern Religious Experience -- Bibliography -- Katalin Luffy (''Lucian Blaga'' Zentrale Universitätsbibliothek, Klausenburg): Von Süddeutschland nach Klausenburg:. Zur Geschichte der Handschrift Ms.683 -- Bibliographie -- Regina Cermann (Österreichische Akademie der Wissenschaften, Institut für Mittelalterforschung, Abteilung Schrift- und Buchwesen): Individualstück oder Standardware?. Über das deutschsprachige Gebetbuch Ms.683 in Klausenburg -- Anhang 1. -- Anhang 2. -- Anhang 3. -- Bibliographie -- Etablierte Literaturkürzel -- Fotostrecke -- Adrian Papahagi (Babeş-Bolyai University of Cluj, Romania): A Medieval Flemish Book of Hours in Early Modern Transylvania (MS 684, Lucian Blaga Central University Library, Cluj) -- Appendix Contents of Cluj, BCU, MS 684 -- Bibliography -- Constantin Ittu (Lucian Blaga University of Sibiu, Romania): A Sixteenth-Century Devotional Book: the Brukenthal Breviary -- Bibliography -- Kata Ágnes Szűcs (University of Szeged, Hungary): Saint Elizabeth of Hungary in Flemish Books of Hours -- A possible origin of the motif -- Conclusion and further questions -- Bibliography -- Illustrations -- Volker Leppin (Yale Divinity School): Eine Untersuchung anhand des Hortulus animae -- Der Hortulus animae, Nürnberg, 1519 -- Regulierung des äußeren Alltags -- Formen äußerlich quantifizierter Frömmigkeit -- Übergänge: Ablassverheißung als Anreiz für innerliche Frömmigkeit -- Formierung des Inneren -- Schlussüberlegungen -- Bibliographie.